Designing of Evaporator Length in Very Low Temperature Chest Freezer by using Environmentally Friendly Refrigerant R290 - Sumeru, Kasni; Nugraha, Ridwan; Badarudin, Apip; Simbolon, Luga Martin; bin Sukri, Mohamad Firdaus; Yuningsih, Nani (Jurnal Polimesin, 2023)
Chest freezers generally use R600a or R134a as working fluids. When using R600a, the minimum cabin temperature is only -10oC, whereas when using R134a, it can reach -25oC. The purpose of this study is to calculate the evaporator length of a chest freezer that uses R290 as a refrigerant so that its cabin temperature can reach below 35 oC, lower than the cabin temperature of a typical chest freezer. Calculation of the evaporator pipe length is done using the forced convection heat transfer equation to calculate the heat transfer coefficient inside the evaporator pipe and natural heat transfer to calculate the heat transfer coefficient outside the evaporator pipe.  Based on the calculations, the chest freezer has a compressor capacity of 200 W, an evaporator length of 3.57 m, and a diameter of 3/8 inch or 9.52 mm. The test results show that the temperature of the chest freezer cabin can reach -36oC in the 36th minute with a cooling capacity of 289 W, while the input power and COP are 198 watts and 1.46, respectively. Compared to R134a, the use of R290 is more advantageous. In addition to lower cabin temperatures, it is also much more environmentally friendly, because the GWP (global warming potential) value of R134a is much higher than that of R290. It means that the use of R290 as a working fluid in the chest freezer will significantly reduce emissions of gases that cause global warming.